The shape of D-glucosamine - Peña, Isabel (2014)
The bioactive amino monosaccharideD-glucosamine has been generated in the gas phasevialaserablation ofD-glucosamine hydrochloride. Three cyclica-4C1pyranose forms have been identified usingFourier transform microwave techniques. Stereoelectronic hyperconjugative forces – essentially linkedwith the anomeric orgaucheeffect – and cooperative OH O, OH N and NH O chains, extendedalong the entire molecule, are found to be the main factors driving the conformational behavior. Theorientation of the NH2group within each conformer has been determined by the values of the nuclearquadrupole coupling constants. The results have been compared with those recently obtained for thearchetypicalD-glucose.